Direct observation of large electron–phonon interaction effect on phonon heat transport - Jiawei Zhou (Nature Portfolio, 2020)
To what extent the charge carriers can alter phonon heat conduction at environmental temperatures through electron–phonon interactions is an open question. Here, the authors demonstrate substantial reduction in thermal conductivity at high charge carrier densities due to significant phonon scatterings by electrons.